Randomizing information on a targeted wage support program for older workers: A field experiment - Gesine Stephan; Gerard van den Berg; Pia Homrighausen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
To address the problem of high reservation wages among older unemployed individuals, a German targeted wage support program aimed at providing incentives to accept lower paid wage offers. We sent out information brochures on this program to randomly selected eligible men. The treatment significantly increased awareness of the program by 20 percentage points. Combining survey and administrative data, we conduct reduced form estimates of the effects of brochure receipt on recipients and estimate local average treatment effects of additional program knowledge. The information treatment significantly increased take-up rates of the program. For unemployed men aged 50–54, we find no positive effects on employment outcomes, thus the additional take-up seems to have been pure windfall. For unemployed men aged 55–59, however, we find some positive effects of additional information on labor market results. The labor market status of unemployed men above age 60 is not affected by brochure receipt.
Keywords: J64; J65; J68; 330